A rare complication following maxillary third molar extraction: infratemporal fossa abscess - Görkem Müftüoğlu (Cumhuriyet Dental Journal, 2012)
Infratemporal fossa abscess formation is a very rare and life threatening condition and also its differential diagnosis is a very difficult process. Infratemporal fossa abscess following the non-infected, asymptomatic, erupted maxillary third molar extraction in a young and healthy patient is an unexpected and unusual complication. A 25 years old, male patient with a significant infratemporal fossa abscess and his treatment protocol was presented in this case report.